Upper-body strength and range of motion are associated with sprint-paddling force and performance in competitive female and male surfers - Gosney, S.; Parsonage, J.; Worsey, M.; Keogh, J.; MacDonald, L.; Denny, A.; Minahan, C. (The Journal of Strength and Conditioning Research, 2025)
Greater upper-body strength has been linked to superior sprint-paddling performance; however, this relationship in female surfers, and the implications of isolated shoulder strength and range of motion, alongside tethered force, are yet to be explored. Thirty-two competitive Australian surfboard riders (i.e., n = 16 female and n = 16 male surfers) considered "Highly Trained/National," "Elite/International" or "World Class" completed water-based and dryland testing protocols. Water-based testing consisted of 15-m sprint-paddling efforts and 12-second stationary sprint-paddling tethered force efforts, whereas dryland testing consisted of upper-body strength testing (i.e., 1 repetition maximum [1RM] pull-up and isometric internal [IR] and external rotation [ER] shoulder strength) and shoulder range of motion (ROM). Tethered force and upper-body strength measures were expressed as absolute values and relative to surfers' bodyweight. Lasso regression and machine learning analyses determined the tethered force and upper-body strength and ROM variables that indicated faster 5-, 10-, and 15-m sprint-paddling split times (p < 0.05). Analyses revealed that relative measures were superior in identifying variables significantly contributing to sprint-paddling split times and were better at predicting these split times. Greater relative mean tethered force, isometric shoulder strength and ROM ER:IR ratios, as well as relative and absolute 1RM pull-up significantly contributed to faster split times for all surfers. Greater isometric shoulder strength ratios were more indicative of faster split times for male surfers, whereas greater shoulder ROM ratios were more indicative for female surfers. These findings may allow coaches to better implement evidence-informed training strategies into the daily training environment to optimize sprint-paddling performance for female and male surfers.